HISTORY OF THE RUSSIAN CENTRAL BANKS AS DEVELOPMENT INSTITUTIONS (1860-1991) - S. Matveevskij (Вестник университета, 2018)
The activities of the central bank of Russia for the period since 1860 for 1991 has deen analyzed. It was concluded that the author concludes that the state banks of Russia both during the Russian Empire and after 1917 in addition to the special func-tions of central banks, constantly implemented the functions of development banks. It was suggested using this historical experience to accelerate economic growth in Rus-sia. It is proposed to expand the funding of existing (Vneshekonombank, the Industri-al Development Fund) and new development institutions by issuing and selling bonds. Using the experience of international multilateral banks in selecting and supporting investment projects will improve the eciency of Russian development institutions.